2007
DOI: 10.1007/s00125-007-0668-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the peroxisome proliferator-activated receptor δ gene in relation to common metabolic traits in 7,495 middle-aged white people

Abstract: Aims/hypothesis Studies in animals reveal that peroxisome proliferator-activated receptor δ (PPARδ) regulates glucose metabolism and insulin sensitivity in both the liver and skeletal muscles. Moreover, PPARδ augments physical endurance and increases oxidative metabolism, thereby averting obesity. Thus, we hypothesised that common variation in the PPARD gene is associated with insulin resistance and metabolic traits. Materials and methods We studied variation in the exonic region of PPARD. Based upon the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
(54 reference statements)
5
25
0
Order By: Relevance
“…Similar with our study, several studies from other populations reported the lack of association of PPARδ T294C SNP with obesity, 38,47 Met-S and their related clinical variables. 47 Meanwhile, other studies found significant association with obesity, 46,[48][49][50] increased plasma LDL-C, 6,51 and decreased plasma HDL-C. 6,49 When participants with homozygous wild type for all the three SNPs were clustered together to compare with those with at least one mutant allele, no significant differences in the anthropometric and clinical measurements were observed. This finding suggests that polygenic obesity and Met-S have a multi-factorial etiology that involves complex interactions between many candidate genes, hormonal status, dietary habits, and other environmental factors.…”
Section: Ppar Gene Variants and Obesity In Malaysians -Chia Et Alsupporting
confidence: 92%
“…Similar with our study, several studies from other populations reported the lack of association of PPARδ T294C SNP with obesity, 38,47 Met-S and their related clinical variables. 47 Meanwhile, other studies found significant association with obesity, 46,[48][49][50] increased plasma LDL-C, 6,51 and decreased plasma HDL-C. 6,49 When participants with homozygous wild type for all the three SNPs were clustered together to compare with those with at least one mutant allele, no significant differences in the anthropometric and clinical measurements were observed. This finding suggests that polygenic obesity and Met-S have a multi-factorial etiology that involves complex interactions between many candidate genes, hormonal status, dietary habits, and other environmental factors.…”
Section: Ppar Gene Variants and Obesity In Malaysians -Chia Et Alsupporting
confidence: 92%
“…This risk was more pronounced in combination with SNPs of the PPARGC1A and PPARG2 genes (Andrulionyte et al, 2006). On the other hand, Grarup et al (2007) found no major effect of SNPs in PPARD on the risk for type 2 diabetes. Again, this is in line with the absence of finding the PPARD in GWAS for type 2 diabetes.…”
mentioning
confidence: 78%
“…Because PPAR␦ is an important regulator of genes involved in lipid and glucose metabolism, one might expect polymorphisms in PPARD to be associated with the metabolic syndrome, type 2 diabetes, obesity, and/or cardiovascular disease. Several association studies on the role of PPARD polymorphisms in relation to metabolic dysfunction and risk for diabetes and cardiovascular disease have been published (Skogsberg et al, 2003a,b;Shin et al, 2004;Gouni-Berthold et al, 2005;Vä nttinen et al, 2005;Aberle et al, 2006a,b;Andrulionyte et al, 2006;Hu et al, 2006;Grarup et al, 2007;Hautala et al, 2007;Robitaille et al, 2007;Stefan et al, 2007;Lagou et al, 2008;Sá ez et al, 2008;Thamer et al, 2008). More than 16 SNPs in PPARD have been analyzed thus far, and the majority of these relatively large association studies have investigated a polymorphism in exon 4, rs2016520, located 87 base pairs upstream of the translational start site.…”
Section: B Single-nucleotide Polymorphisms In Peroxisome Proliferatomentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants of WFS1 (rs10010131) and EXT2 (rs11037909, rs1113132, rs37408788) were significantly associated with type 2 diabetes in several studies [15,22,23]. Genetic variants of MTTP (rs1800804) and PPARD (rs1053049, rs2016520, rs2076167, rs34474204, rs6902123) were selected since they have been shown to be involved in ischemic heart disease, glucose and lipid metabolism [24][25][26][27][28][29]. Likewise, genetic variants near HHEX (rs7923837, and rs1544210) were associated with type 2 diabetes in several linkage studies [15,19,30].…”
Section: Stockholm Diabetes Prevention Program Controls (Sdpp)mentioning
confidence: 99%